Effectiveness of Online Learning in English Subject at Pangkalpinang state Junior High School during Covid-19 Pandemic - Juriana Juriana; Firdaus Firdaus (Sustainable, 2023)
Effective online learning is virtual face-to-face learning carried out through communication and information technology by teachers and students since the emergence of the Covid-19 pandemic by fulfilling 5 indicators (management of learning implementation, communicative processes, student responses, learning activities and learning outcomes) which are supported by adequate infrastructure (Internet network, smartphone memory, internet quota) especially English language learning. Is the implementation of online English learning effective at Pangkalpinang State Middle School? remembering that there were several obstacles found in the field, namely difficult networks, full smartphone memory, insufficient internet quota, bad weather such as thunderstorms, and the absence of students' parents to accompany them during the learning process. This research is a mix-method research that uses a questionnaire distributed via WhatsApp as a data collection method. The questionnaire contains 8 closed questions and 3 open questions. The population contains all state junior high school students in Pangkalpinang. Samples were taken using cluster random sampling. The data analysis technique used is descriptive statistical analysis, the results of which are developed using qualitative analysis.